Investigation of rectangular shape object detection and classification using python - Zulkefle, Mohamad Hafizie; Abdul Ghani, A. S. (Penerbit UMP, 2022)
The existing fishcake machine can perform tasks to increase the productivity of fishcakes in the market. However, high productivity is not the only main purpose of a successful food manufacturing industries. The quality of the food itself need to accommodate the standard quality that has been lined by authorities to ensure that the quality of the food product must be at the best standard along with its high productivity. The objective of this work is to develop a monitoring method for detection of irregular shape and foreign particles of the fishcake during the fishcake production. This work will implement and uses both hardware and software elements to provide the best solution for the purpose of fishcake quality sustainability. Real-time image processing is the method used in this study by developing python program through Raspberry Pi 4. The algorithm of the programming is the main concern in this research. The library used for this study is OpenCV which is a common API used for computer vision.